Найдите значение выражения p(a)/p(6-a)/, если p(a)=a(6-a)/a-3

Найдите значение выражения p(a)/p(6-a)/, если p(a)=a(6-a)/a-3

  • P(a)=a(6-a)
    a-3
    p(6-a)=(6-a)(6-(6-a)) =(6-a)(6-6+a) =a(6-a)
    (6-a)-3 6-a-3 3-a
    p(a) = a(6-a) : a (6-a) = a(6-a) * -(a-3) = -1
    p(6-a) a-3 3-a a-3 a(6-a)

    Ответ: -1.

  • P(6-a)=(6-a)(6-6+a)/(6-a-3)=a(6-a)/(3-a)
    p(a);p(6-a)=a(6-a)/(a-3):a(6-a)/(3-a)=a(6-a)/(a-3)*(3-a)/a(6-a)=-1

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *